2012
DOI: 10.1097/ana.0b013e318224030a
|View full text |Cite
|
Sign up to set email alerts
|

Are Optimal Cerebral Perfusion Pressure and Cerebrovascular Autoregulation Related to Long-term Outcome in Patients With Aneurysmal Subarachnoid Hemorrhage?

Abstract: The assessment of CVA and CPPopt is feasible in aSAH patients and may provide important information regarding long-term outcome. A PRx above the 0.2 threshold and a CPP below the CPPopt range are associated with worse outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…29 In addition to these pharmacological interventions, managing blood pressure at individually required optimal CPP levels has been suggested as a therapeutic hemodynamic target with the potential to improve both autoregulation and outcome. 18,30 …”
Section: Discussionmentioning
confidence: 99%
“…29 In addition to these pharmacological interventions, managing blood pressure at individually required optimal CPP levels has been suggested as a therapeutic hemodynamic target with the potential to improve both autoregulation and outcome. 18,30 …”
Section: Discussionmentioning
confidence: 99%
“…It is possible that a subpopulation of patients with acute stroke with relative intact CA may benefit from aggressive blood pressure treatment to improve clinical outcome and decrease harmful side effects. It is also not known if similar to acute stroke, an ‘optimal ABP’ which assures best CA exists and can be assessed using continuous monitoring 30. This critical knowledge gap further supports the need to understand the complex mechanisms of CA on an individual basis and apply to patient care in an era of precision medicine.…”
Section: Clinical Applications Of Ca Studies In Strokementioning
confidence: 99%
“…Some have reported that clotted blood and fluid buildup in the subarachnoid space increase ICP, whereas others have reported that blockage of the normal CSF circulation causes enlargement of the ventricles and elevation of ICP [1,3]. Furthermore, recent studies have shown that cerebral vasospasm following aSAH plays an important role in the elevation of ICP [19][20][21]. However, whether the accumulation of subarachnoid hemorrhage causes an increase in ICP has yet to be determined.…”
Section: Discussionmentioning
confidence: 93%